Antioxidant and antitumor activities of Polyalthia simiarum (Buch.-Ham. ex Hook. F. & Thomson) Hook. F. & Thomson - Zahan, Ronok; Kabir, Seiina; Mosaddik, Ashik; Chowdhury, Abdullah Mohammad Sarwaruddin; Hasan, Choudhury Mahmood; Rashid, Mohammad Abdur (© 2013 Turkish Journal of Pharmaceutical Sciences, 2016)
This article was published in Turkish Journal of Pharmaceutical Sciences [© 2013 Turkish Journal of Pharmaceutical Sciences] and the definite version is available at: http://journal.teb.org.tr/1032013(3)%20405-414.pdf The article website is at: http://journal.eczakademi.org